PENGARUH KONSELING TERHADAP PENGETAHUANIBU DALAM PERAWATAN BAYI BERAT BADAN LAHIR RENDAH DI RUANGAN NHCU RSUD PROF DR. W. Z. JOHANNES KUPANG - Marselina Intan (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2021)
The results of Indonesia's demographic and health survey of infant mortality rates were 34/1000 live births, far from the MDG target (23/1000 live births). The main causes of infant death are asphyxia, premature babies, Low Birth Weight and infections. The efforts made by the government to reduce infant mortality in 2018 are PRONAS. Efforts are being made to reduce the infant mortality rate at RSF PROF Dr. W. Z. Johannes Kupang with PONEK services. The purpose of this study is to find out the differences in mother's knowledge before being given counseling about Low Birth Weight care and after being given Low Birth Weight care counseling. The study design used one group pretest and posttest design, conducted on 30 samples of mothers with Low Birth Weight infants. Statistical tests using Wilcoxon with the results, p = 0,000, where the data is said to have an effect if p <0.05, then H1 is accepted meaning there is an influence. The results showed that prior to being given counseling knowledge of the mother (66.7%) and after being given counseling increased (96.7%). Conclusion: There is an effect of counseling on mother's knowledge after counseling is given. Recommended: for nurse in the nhcu room to always provide regular counseling for every mother with LBW when treated and before going home. Keywords: knowledge of Low Birth Weight counseling